(untitled) (Economic and Political Thought, 2010)
The article presents the experience gained by Germany and France in connection with the introduction of the common currency and its implications for Poland. The author briefly describes the route of Germany and France to the euro. Next, she discusses political and social results of the substitution of the mark and the franc by the euro, i.e. on the one hand an issue of national sovereignty, democratic legitimization and deficit, Europeanization of policies, elites and political institutions and the increase in the role of the European Union in the world, on the other hand modification of the European social model, sense of collective deprivation, mental and behavioral change, strengthening of the European identity and practical adjustments. The author comments on the issue of real inflation and that perceived by the German and French societies and she presents the results of the research into the social attitudes towards the euro at that time. She proves that the pessimistic predictions that the Germans and French would have great problems with the substitution of their national currencies by a common one failed to materialize. The article ends with an assessment of the use of the common currency so far and gives recommendations for Poland.